Experimental vapor-liquid equilibria data for binary mixtures of xylene isomers - Rodrigues,W.L. (2005)
Separation of aromatic C8 compounds by distillation is a difficult task due to the low relative volatilities of the compounds and to the high degree of purity required of the final commercial products. For rigorous simulation and optimization of this separation, the use of a model capable of describing vapor-liquid equilibria accurately is necessary. Nevertheless, experimental data are not available for all binaries at atmospheric pressure. Vapor-liquid equilibria data for binary mixtures were isobarically obtained with a modified Fischer cell at 100.65 kPa. The vapor and liquid phase compositions were analyzed with a gas chromatograph. The methodology was initially tested for cyclo-hexane+n-heptane data; results obtained are similar to other data in the literature. Data for xylene binary mixtures were then obtained, and after testing, were considered to be thermodynamically consistent. Experimental data were regressed with Aspen Plus® 10.1 and binary interaction parameters were reported for the most frequently used activity coefficient models and for the classic mixing rules of two cubic equations of state.